Jobs and Land Use within Cities : A Survey of Theory, Evidence, and Policy - Grover Goswami, Arti; Lall, Somik V. (Published by Oxford University Press on behalf of the World Bank, 2021)
Over the last century, the urban spatial structure of cities has transformed dramatically from a traditional monocentric configuration to varying forms of decentralized organization. This paper reviews theory and empirical evidence to understand the urban morphology of jobs and land use within a city. Our survey highlights four broad insights: (i) The evolution of monocentric to polycentric centers have been accompanied by structural changes within the city. (ii) The internal geography of a city is an outcome of the trade-off between the pull from agglomeration economies and the push from congestion. (iii) The presence of externalities implies that the equilibrium spatial organization achieved by profit-maximizing firms may not necessarily be optimal. This justifies the role of public policy in addressing associated market failures. (iv) The productive edge and competitiveness of a city can be enhanced by introducing policies that increase the overall connectivity to take advantage of economic opportunities across the metropolitan area. The survey also puts together a wide range of policy instruments useful in closing the gap between equilibrium urban spatial structures and the optimal outcome.